Implementation of Trend Moment Method in Forecasting Regional Income - Sutrisman Sutrisman; Havid Syafwan; Rohminatin Rohminatin (Building of Informatics, Technology and Science (BITS), 2022)
In order to carry out the functions and authorities of local governments in the form of implementing fiscal authority, regions must be able to recognize potential and identify the resources they have. Forecasting is an art and science in predicting future events. The Regional Financial and Asset Management Agency (BPKAD) of Asahan Regency does not yet know the Regional Revenue in the upcoming period & is not yet available a system that can calculate Regional Revenue for the upcoming period. The main purpose of this research is to know the prediction of Regional Income in the following year. The system created helps in determining Regional Revenue in 2022, with data used from 2011 – 2021. The Trend Moment method is a method that uses certain statistical and mathematical calculation methods to find out the function of a straight line instead of a broken line formed by the company's historical data. In choosing the forecast method, accuracy is needed to minimize errors in forecasting (forecast error), the goal is that the forecast can approach reality. Based on the results of system testing, this Regional Revenue Forecasting predicts regional revenue in 2022, which is IDR 136,847,395,228.82 and the result of the percentage of errors (MAPE) Mean Absolute Percentage Error of 0.12%.